BAP1-Altered Malignant Pleural Mesothelioma: Outcomes With Chemotherapy, Immune Check-Point Inhibitors and Poly(ADP-Ribose) Polymerase Inhibitors - Dudnik, Elizabeth; Bar, Jair; Moore, Assaf; Gottfried, Teodor; Moskovitz, Mor; Dudnik, Julia; Shochat, Tzippy; Allen, Aaron M.; Zer, Alona; Rotem, Ofer; Peled, Nir; Urban, Damien (Frontiers in Oncology, 2021)
Objectives: Little is known regarding the outcomes of systemic treatments in BAP1-altered malignant pleural mesothelioma (MPM). Materials and Methods: 45 patients with MPM (group A: 8 MPM patients with BAP1 inactivating mutation/copy number loss [FoundationOne® CDx/TEMPUSxT], selected from the electronic databases of 4 Israeli cancer centers (ICC); group B: 37 consecutive [years 2016-2018] MPM patients selected from the electronic databases of 2 ICC - of those 6 patients without a BAP1 alteration [group B1] and 31 patients not tested for BAP1 [group B2]) were analyzed for ORR, PFS (mRECIST) and OS with 1st-line platinum/pemetrexed+/-antiangiogenic drug (CT, n-28), immune checkpoint inhibitors (ICPi, n-16) and poly (ADP-ribose) polymerase inhibitors (PARPi, n-4). OS since diagnosis (OSDx) was assessed. Results: There were no differences in ORR or mPFS with CT between the groups: ORR-50% vs 47% vs 50% vs 47% (p>0.9), mPFS-9.1mo (95%CI, 1.2-16.1) vs 9.2mo (95%CI, 2.9-13.3) vs 7.2mo (95% CI, 2.3- NR) vs 10.9mo (95% CI, 2.9-20.3) (p>0.8) in groups A, B, B1, and B2, respectively. There were no differences in ORR or mPFS with ICPi between the groups: ORR-0% vs 27% vs 33% vs 25% (p>0.2), mPFS-2.5mo (95%CI, 1.4-3.7) vs 3.0mo (95%CI, 1.3-10.5) vs 2.0mo (95% CI, 1.9-NR) vs 4.5mo (95% CI, 0.3-10.5) (p>0.3) in groups A, B, B1, and B2, respectively. In group A, no responses were seen with PARPi; mPFS with PARPi was 1.8mo (95%CI, 1.8-NR). OSDx was 98.3mo (95% CI, 9.7-98.3) vs 19.4mo (95% CI, 9.7-47.3) vs 18.8mo (95% CI, 8.5-NR) vs 19.5mo (95% CI, 8.3-82.2) in groups A, B, B1, and B2, respectively (p>0.3). Conclusions: BAP1-altered MPM, as compared to non-selected MPM, is characterized by similar efficacy of CT and ICPi. Numerically longer OS in BAP1-altered MPM may reflect favorable tumor biology. No responses were observed with PARPi.